Prevalence of specific human papillomavirus genotypes among Moroccan women with invasive cervical cancer - Kaoutar Anouar Tadlaoui; Mustapha Benhessou; Abdelilah Laraqui; Lina Benfdil; El Arbi Bouaiti; Mohammed El Mzibri; Moulay Mustapha Ennaji (Open Exploration Publishing Inc., 2024)
Aim: The aim of this study is to investigate the prevalence of human papillomavirus (HPV) genotypes in Moroccan women diagnosed with invasive cervical cancer and to assess the association between HPV infection and some socio-demographic characteristics and clinicopathological features. Methods: In this study, 80 fresh biopsies from patients with confirmed diagnoses of cervical cancer during the study period (2020-2021) were collected. All cases were subject to HPV detection by nested PCR using MY09/11 and GP5+/6+ primers. HPV genotyping was performed by type-specific PCR targeting HPV 6, 11, 16, 18, 31, and 33. Results: The average age of patients was 54 years. Most patients were diagnosed with squamous cell carcinoma (SCC; 82.5%) at stage II (71.3%). Overall, 91.3% of cervical cancer cases were HPV-positive. HPV 16 is the most prevalent genotype, reported in 60.3% of HPV-positive cases, followed by HPV 18, 33, and 31 genotypes, identified in 20.5%, 12.3%, and 6.8%, respectively. No double infection with these genotypes was observed. Statistical analysis showed a significant correlation between HPV infection and age at menarche (P = 0.028), parity (P = 0.004), childbirth delivery (P = 0.040), and marital status (P = 0.042). Conclusions: HPV-DNA was prevalent in most examined cervical cancer tissues and HPV 16, HPV 18, HPV 33, and HPV 31 were present, at single infection, in all HPV-positive cases. These results emphasize already reported data on HPV distribution in Morocco and may contribute significantly to promoting the use of HPV DNA-based screening tests and available vaccines to limit HPV infection, viral dissemination, and cancer cervical development.